2014
DOI: 10.20529/ijme.2014.047
|View full text |Cite
|
Sign up to set email alerts
|

Establishing institutional ethics committees: challenges and solutions–a review of the literature

Abstract: This review of the literature was conducted to identify the challenges faced while establishing institutional ethics committees (IECs) as well as to suggest some solutions. The search of the literature was carried out with the help of the PubMed search engine, using “research ethics committees” (MeSH] and “India” (MeSH]) as the key words for articles published between 2004 and 2012. We found 31 articles related to the topic, and the most common challenge mentioned was inappropriate functioning of IECs (n=17), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Literature review enlisted challenges which included improper knowledge of appointment of committee members, availability/scarcity of trained legal expert and layperson in the quorum and very few consultant having the research background with no formal training in GCP. [45] Most of the challenges faced during IEC set up remained same however few well trained and experienced IEC external members guided in selection of quorum. Major hurdle of training of new members in SOP and IEC review procedure was accomplished with help of experienced external members.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review enlisted challenges which included improper knowledge of appointment of committee members, availability/scarcity of trained legal expert and layperson in the quorum and very few consultant having the research background with no formal training in GCP. [45] Most of the challenges faced during IEC set up remained same however few well trained and experienced IEC external members guided in selection of quorum. Major hurdle of training of new members in SOP and IEC review procedure was accomplished with help of experienced external members.…”
Section: Discussionmentioning
confidence: 99%
“…A review[ 24 ] identified 31 articles published between 2004 and 2012 related to the topic of the challenges faced while establishing Institutional ECs (IECs) and their functioning. The most common challenge mentioned in these articles was inappropriate functioning of IECs ( n = 17), followed by inappropriate structure ( n = 14).…”
Section: The Past (2005–2013)mentioning
confidence: 99%
“…Several studies on performance of Indian ECs have reported deficiencies in EC functioning,[23] for example, inappropriate composition and functioning, inadequate training, conflict of interest, lack of standard operating procedures, deficiencies in approval letters. However, these studies were conducted before the registration of ECs.…”
mentioning
confidence: 99%